Ursodeoxycholic acid therapy in intrahepatic cholestasis of pregnancy: Results in real-world conditions and factors predictive of response to treatment. Issue 1 (January 2017) - Bacq, Yannick; le Besco, Matthieu; Lecuyer, Anne-Isabelle; Gendrot, Chantal; Potin, Jérôme; Andres, Christian R.; Aubourg, Alexandre
Abstract: Background: Ursodeoxycholic acid (UDCA) therapy is commonly used in intrahepatic cholestasis of pregnancy (ICP). Aim: To evaluate the efficacy and tolerance of UDCA in real-world conditions and to search for factors predictive of response to treatment. Methods: This observational study included 98 consecutive patients suffering from pruritus during pregnancy associated with increased ALT levels or total bile acid (TBA) concentrations, without other causes of cholestasis. The entire ABCB4 gene coding sequence was analyzed by DNA sequencing. Results: UDCA was prescribed until delivery in all patients (mean dose 14.0 mg/kg/day; mean duration 30.4 days). Pruritus improved in 75/98 (76.5%) patients, and totally disappeared before delivery in 25/98 (25.5%). After 2–3 weeks of treatment, ALT levels decreased by more than 50% of base line in 67/86 (77.9%) patients and normalized in 34/86 (39.5%), and TBA concentrations decreased in 28/81 (34.6%). Only one patient stopped the treatment before delivery. On multivariate analysis, ALT >175 IU/l before treatment was associated with improvement of pruritus (OR 2.97, 95% CI 1.12–7.89, P = 0.029) and with decreased ALT (OR 18.61, 95% CI 3.94–87.99, P = 0.0002). ABCB4 gene mutation was not associated with response to treatment. Conclusion: This study supports the use of UDCA as first line therapy in ICP.